The Spatial‐Temporal Alternative Splicing Profile Reveals the Functional Diversity of FXR1 Isoforms in Myogenesis - Wei Wang; Xinhao Fan; Weiwei Liu; Yuxin Huang; Shuhong Zhao; Yalan Yang; Zhonglin Tang (Advanced Science)
Abstract Alternative splicing (AS) is a fundamental mechanism contributing to proteome diversity, yet its comprehensive landscape and regulatory dynamics during skeletal muscle development remain largely unexplored. Here, the temporal AS profiles are investigated during myogenesis in five vertebrates, conducting comprehensive profiling across 27 developmental stages in skeletal muscle and encompassing ten tissues in adult pigs. The analysis reveals a pervasive and evolutionarily conserved pattern of alternative exon usage throughout myogenic differentiation, with hundreds of skipped exons (SEs) showing developmental regulation, particularly within skeletal muscle. Notably, this study identifies a muscle‐specific SE (exon 15) within the Fxr1 gene, whose AS generates two dynamically expressed isoforms with distinct functions: the isoform without exon 15 (Fxr1E15−) regulates myoblasts proliferation, while the isoform incorporating exon 15 (Fxr1E15+) promotes myogenic differentiation and fusion. Transcriptome analysis suggests that specifically knocking‐down Fxr1E15+ isoform in myoblasts modulates differentiation by influencing gene expression and splicing of specific targets. The increased inclusion of exon 15 during differentiation is mediated by the binding of Rbm24 to the intron. Furthermore, in vivo experiments indicate that the Fxr1E15+ isoform facilitates muscle regeneration. Collectively, these findings provide a comprehensive resource for AS studies in skeletal muscle development, underscoring the diverse functions and regulatory mechanisms governing distinct Fxr1 isoforms in myogenesis.